Penerapan Program Linier untuk Menyelesaikan Masalah Alokasi Sumber Daya Pada Persoalan Penugasan - Bayhaqi Yasri; Fauziah Mawaddah Harefa; Maulia Fadila; Nazira Ananda; Siti Salamah Br Ginting (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Efficient resource allocation is a major challenge in various sectors, especially when faced with limitations in quantity, time, and cost. This study aims to examine the application of linear programming as an optimization method in solving assignment problems, where a number of resources must be optimally allocated to a number of specific tasks. Through a literature study approach, this study examines various relevant previous study results, especially in the Indonesian context. The results of the study indicate that linear programming is able to improve operational efficiency, reduce costs, and produce a more balanced task distribution. However, this model has limitations in dealing with non-linear conditions and data uncertainty, so integration with other methods such as fuzzy logic or genetic algorithms is needed. This study is expected to broaden the understanding of the benefits of linear programming and encourage its wider application in quantitative-based decision making.